Estimation of Pore Pressure and In-Situ Stresses for Halfaya Oil Field: A Case Study - Maytham I. Saddam; Ghanim M. Farman (Zien Journals, 2022)
Formation pressure is the pressure of fluid in rock pores. As a geologic parameter, formation pressure plays an important role in exploration activity, drilling engineering and oil/gas field development. For drilling engineering, formation pore pressure is an indispensable parameter for rapid, safe, and economic drilling, so it is very important to forecast formation pressure precisely. Stratigraphy is always in a triaxial stress, it can be expressed by the principal stress in three directions. That is the maximum horizontal principal stress, the minimum horizontal principal stress and the vertical stress. In the horizontal direction exists extrusion stress approximately perpendicular to the long axis of the anticline, namely NNESSW direction. The three main stresses should be relatively homogeneous, and there is no great difference.
Keywords: Geologic parameter; Pore pressure; Vertical stress; Homogeneous